CO-PO Mapping and Attainment Booklet for Tier-II Students with Rubrics Assessment - Kulkarni, V. A.; Ahuja, B. B.; Dhanvijay, M. R. (Journal of Engineering Education Transformations, 2017)
National Board of Accreditation, June 2015 format has mandated Outcome Based Education (OBE) after India is full signatory member of Washington Accord in 2014. Tier-II students are facing tough competitions from Tier-I students with respect to attainment of knowledge and involvement of technical aspects and gap visible with respect to employability of students. CO-PO mapping and attainment, defined by NBA, gives substantial opportunity for Tier-II students to bridge this gap of employability. In this present paper, a case study is developed through COPO mapping and attainment for SE Production Students of Tier-II. The formulated rubrics assessment is indicative of continuous improvement strategy that can be easily adoptable by faculty and students across engineering streams.